Molecular Underpinnings of Fe(III) Oxide Reduction by Shewanella Oneidensis MR-1 - Shi, Liang; Rosso, Kevin M.; Clarke, Thomas A.; Richardson, David J.; Zachara, John M.; Fredrickson, James K. (Frontiers in Microbiology, 2012)
In the absence of O2 and other electron acceptors, the Gram-negative bacterium Shewanella oneidensis MR-1 can use ferric [Fe(III)] (oxy)(hydr)oxide minerals as the terminal electron acceptors for anaerobic respiration. At circumneutral pH and in the absence of strong complexing ligands, Fe(III) oxides are relatively insoluble and thus are external to the bacterial cells. S. oneidensis MR-1 has evolved the machinery (i.e., metal-reducing or Mtr pathway) for transferring electrons across the entire cell envelope to the surface of extracellular Fe(III) oxides. The protein components identified to date for the Mtr pathway include CymA, MtrA, MtrB, MtrC and OmcA. CymA is an inner-membrane tetraheme c-type cytochrome (c-Cyt) that is proposed to oxidize the quinol in the inner-membrane and transfers the released electrons to redox proteins in the periplasm. Although the periplasmic proteins receiving electrons from CymA during Fe(III) oxidation have not been identified, they are believed to relay the electrons to MtrA. A decaheme c-Cyt, MtrA is thought to be embedded in the trans outer-membrane and porin-like protein MtrB. Together, MtrAB deliver the electrons across the outer-membrane to the MtrC and OmcA on the outmost bacterial surface. Functioning as terminal reductases, the outer membrane and decaheme c-Cyts MtrC and OmcA can bind the surface of Fe(III) oxides and transfer electrons directly to these minerals. To increase their reaction rates, MtrC and OmcA can use the flavins secreted by S. oneidensis MR-1 cells as diffusible co-factors for reduction of Fe(III) oxides. MtrC and OmcA can also serve as the terminal reductases for soluble forms of Fe(III). Although our understanding of the Mtr pathway is still far from complete, it is the best characterized microbial pathway used for extracellular electron exchange. Characterizations of the Mtr pathway have made significant contributions to the molecular understanding of microbial reduction of Fe(III) oxides.